Analysis of Affecting Factors Property Purchase Decision (Study on CitraLand Driyorejo CBD Housing, Gresik) - Cholief Choerrasjani (Universitas Ciputra Surabaya, 2022)
Purchasing decisions are influenced by various factors. Ciputra conveyed that there are 10 principles for customers satisfaction, which became a reference for every residential area development that was built. This study aims to examine the factors that influence property purchase decisions in the CitraLand Driyorejo CBD project. The variables studied were Ciputra's 10 principles: location (X1), lifestyle (X2), product quality (X3), housing facilities (X4), customer participation (X5), developer commitment (X6), developer service (X7), added value (X8), environment (X9) and theme/masterplan (X10). Location has 3 indicators, lifestyle has 4 indicators, product quality has 4 indicators, housing facilities has 4 indicators, customer participation has 3 indicators, developer commitment has 3 indicators, developer services have 4 indicators, added value has 3 indicators, environment has 3 indicators and theme/masterplan has 3 indicators. The analytical tool used in this study is confirmatory factor analysis. The population in this study were all customers who had bought a house in the period July 2019 to December 2019, with the total of 184 customers. The sample was determined by using the census technique, where all 184 customers were used are respondents. The results showed that Ciputra's 10 principles influence purchasing decisions, and no new factors were formed. The order of principles based on priorityof influence on purchasing decisions is lifestyle, added value, developer services, developer commitment, location, customer participation, housing facilities, production quality, theme/masterplan and finally the environment.